1983
DOI: 10.1073/pnas.80.9.2743
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of synthesis of enzymes for de novo fatty acid biosynthesis by an endotoxin-induced mediator from exudate cells.

Abstract: An endotoxin-induced mediator from exudate cells markedly suppresses the activities of the key enzymes for de novo fatty acid biosynthesis-acetyl-CoA carboxylase [acetyl-CoA:carbon dioxide ligase (ADP-forming), EC 6.4.1.2] and fatty acid synthetase-in differentiating 3T3-L1 murine preadipocytes. The loss in activity, at least in part, appears to be due to a specific effect on the synthesis of the enzymes, as determined by a decreased incorporation of [mS] The publication costs ofthis article were defrayed in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 18 publications
0
71
0
Order By: Relevance
“…20 TNF-a was shown to inhibit the synthesis of lipoprotein lipase (LPL), 63 acetyl-CoA-carboxylase (ACC) and fatty acid synthase (FAS). 64 In addition, TNF-a levels were found to be positively associated with UCP2 mRNA expression. 20 All these changes in enzyme activity and gene expression induced by the increased TNF-a in adipose tissue after feeding of CLA favor a decrease in fat cell size.…”
Section: Cla Increases Apoptosis Of Adipocytesmentioning
confidence: 98%
“…20 TNF-a was shown to inhibit the synthesis of lipoprotein lipase (LPL), 63 acetyl-CoA-carboxylase (ACC) and fatty acid synthase (FAS). 64 In addition, TNF-a levels were found to be positively associated with UCP2 mRNA expression. 20 All these changes in enzyme activity and gene expression induced by the increased TNF-a in adipose tissue after feeding of CLA favor a decrease in fat cell size.…”
Section: Cla Increases Apoptosis Of Adipocytesmentioning
confidence: 98%
“…In previous studies we have demonstrated that a macrophage mediator, secreted in response to endotoxin, switched adipose tissue in vivo (11) and 3T3-L1 adipocytes in vitro (3,4) from an anabolic storage mode to a catabolic state. By an unknown mechanism, this macrophage mediator can selectively inhibit the biosynthesis of several anabolic enzymes without adversely affecting the synthesis of most other proteins within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular explanation for this insulin resistance has remained obscure. Recently, we have observed that a form of insulin resistance occurs in 3T3-L 1 adipocytes in culture when these cells are incubated in the presence of a macrophage mediator that is m a d e in response to endotoxin (3,4). We believe that this m a c r o p h a g e mediator functions as a signal to the energy storage cells of the body for selective energy mobilization needed to combat host invasion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rh cachectinlTNF had no effect on total RNA, poly(A)+ RNA, or actin mRNA concentration. It has previously been shown that TNF treatment of 3T3-L1 cultures causes no general effect on total protein synthesis (31,32), and polyacrylamide gel electrophoresis reveals that only a few proteins have visibly different amounts (32).…”
mentioning
confidence: 99%